(untitled) (Revista de História Regional, 2025)
This article aims to rethink the presence of slaves in Petrópolis in the 19th century from a perspective that analyzes the city in symbiosis with the capital Rio de Janeiro. In contrast to most studies about the city in the 19th century and the accounts of travelers of the time, the analysis of the press allows us to identify a city that reproduced within its interior some of the main characteristics of Brazilian urban slavery.